2015
DOI: 10.18553/jmcp.2015.21.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quality Indicators for Dutch Community Pharmacies Using a Comprehensive Assessment Framework

Abstract: BACKGROUND: In 2008, the Dutch Health Care Transparency Programme (Zichtbare Zorg) was set up to develop and apply quality indicators (QIs) for health care. These QIs serve a range of purposes and can be categorized into those for internal use-for meeting quality standards and to continuously measure improvement (formative)-and external use-to enable patients and health insurance companies to distinguish between health care providers (summative). In order to assess the validity of QIs, a comprehensive Indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Figure illustrates the study selection and the exclusion/inclusion processes. The studies were conducted in 12 countries, of which three were conducted in the Netherlands, two each in the UK, USA, and Thailand, and one each in Argentina, Spain, Australia, Canada and Brazil . One study was conducted in three countries: Ethiopia, Uganda and Zimbabwe.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure illustrates the study selection and the exclusion/inclusion processes. The studies were conducted in 12 countries, of which three were conducted in the Netherlands, two each in the UK, USA, and Thailand, and one each in Argentina, Spain, Australia, Canada and Brazil . One study was conducted in three countries: Ethiopia, Uganda and Zimbabwe.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies reported the development of quality indicators for community pharmacies . Multiple methods were used to produce initial sets of indicators including literature review, focus groups, surveys, case studies and interviews (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations